2018
DOI: 10.1002/biof.1414
|View full text |Cite
|
Sign up to set email alerts
|

α‐Tocopherol promotes HaCaT keratinocyte wound repair through the regulation of polarity proteins leading to the polarized cell migration

Abstract: In many developed countries including Japan, how to care the bedridden elderly people with chronic wounds such as decubitus becomes one of the most concerned issues. Although antioxidant micronutrients including vitamin E, especially α-tocopherol (α-Toc), are reported to shorten a period of wound closure, the promoting effect of α-Toc on wound healing independent of its antioxidant activity remains to be fully elucidated. The aim of this study was to examine whether α-Toc affects wound-mediated HaCaT keratinoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…In addition to cell proliferation, an adequate cell migration is also required for the second phase of wound healing for minor, superficial, and basic skin lesions, but also for more complicated pathological states such as ulcers or pressure sores [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cell proliferation, an adequate cell migration is also required for the second phase of wound healing for minor, superficial, and basic skin lesions, but also for more complicated pathological states such as ulcers or pressure sores [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of epithelial cell migration involves several factors and for this process the activation of cytoskeletal remodeling signaling pathways is essential [38][39][40][41][42][43]. In order to establish the mechanism of HT action on the migration stimulation, we determined the expression of crucial proteins involved in the migration process by western blot.…”
Section: Ht Induces Migration-linked Proteins Expressionmentioning
confidence: 99%
“…showed that α-tocopherol (vitamin E) suppressed the growth of murine B16 melanomas in-vitro and in-vivo 27 . It is interesting to note that dl-α-tocopherol stimulated HaCaT wound healing in-vitro and exerted protective properties against skin induced tumorigenesis in mice 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Of these compounds, linolenic acid had the largest peak area (27.97 %) and was followed by tetracosane (–) (8.72 %), 1‐heneicosene (7.69 %), 10‐heneicosene (6.46 %), campesterol (6.35 %), 4‐methyl‐6‐ tert ‐butylphenol (5.77 %), clionasterol (5.60 %), and 1‐tetracosanol (5.15 %; Table 1). Of the 23 identified components in PFFA, hexadecanoic acid, linolenic acid, and vitamin E are reported to promote the migration, proliferation, or skin barrier associated protein formation in many cell types including keratinocytes [29–34] . In addition, cycloartenol, hexadecanoic acid, and vitamin E were implicated in inducing collagen synthesis in cells such as hepatic stellate cells or dermal fibroblasts [29,35–37] .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 23 identified components in PFFA, hexadecanoic acid, linolenic acid, and vitamin E are reported to promote the migration, proliferation, or skin barrier associated protein formation in many cell types including keratinocytes. [29][30][31][32][33][34] In addition, cycloartenol, hexadecanoic acid, and vitamin E were implicated in inducing collagen synthesis in cells such as hepatic stellate cells or dermal fibroblasts. [29,[35][36][37] Therefore, it can be assumed that PFFA may have the ability to facilitate healing and barrier repair-linked responses in wounded skin.…”
Section: Chemical Composition Of Pffamentioning
confidence: 99%